Effective technique of looking for teaching and learning information on the internet - Mat Daud, Nuraihan; Wan Yusof, Wan Putri Zaharah (2009)
When the Internet is mentioned it is often assumed that users know how to search formaterials. Many though experience difficulties in searching for relevant materials. One of the reasons for this is the lack of knowledge on how to search effectively for information. This paper will discuss ways of searching materials using the advanced search facilities of the available search engines and the various metasearch engines. An advanced search allows a user to be more specific about what type of information he is looking for. A metasearch engine is a system that supports unified access to multiple local search engines. Among the metasearch engines are vivisimo, dogpile, profusion, iXqick, cactisearch, Brainboost, kartOO and clusty. They serve to streamline one’s search. A user does not have to scroll through hundreds of pages for useful links. Ways of searching for teaching and learning materials will be shown in this presentation. Such information will help language teachers to look for teaching materials effectively.